Polyvinyl Alcohol Coatings Containing Lamellar Solids with Antimicrobial Activity - Maria Bastianini; Michele Sisani; Raúl Escudero García; Irene Di Guida; Carla Russo; Donatella Pietrella; Riccardo Narducci (Physchem, 2024)
The design of an antimicrobial coating material has become important in the prevention of infections caused by the transmission of pathogens coming from human contact with contaminated surfaces. With that aim, layered single hydroxides (LSHs) and layered double hydroxides (LDHs) containing Zn and Cu intercalated with antimicrobial molecules were synthesized and characterized. Cinnamate and salicylate anions were chosen because of their well-known antimicrobial activity. Several coatings based on polyvinyl alcohol (PVA) and LDHs or LSHs with increasing amounts of filler were prepared and filmed on a polyethylene terephthalate (PET) substrate. The coatings were characterized, and their antimicrobial activity was evaluated against several pathogens that are critical in nosocomial infections, showing a synergistic effect between metal ions and active molecules and the ability to inhibit their growth.